125I Seed Promotes Apoptosis in Non-small Lung Cancer Cells via the p38 MAPK-MDM2-p53 Signaling Pathway - Zhang, Tao; Mo, ZhiQiang; Duan, Guangfeng; Tang, Rijie; Zhang, Fujun; Lu, Mingjian (Frontiers in Oncology, 2021)
Purpose: 125I seeds were effective in the treatment of non-small cell lung cancer in previous research. However, the exact signaling pathway-mediated apoptosis mechanism is still unclear. The present study analyzed the effects and potential mechanisms of 125I seed on the growth and migration of A549 cells. Methods: Lung cancer A549 cells were irradiated with 125I seed for various times. MTT, invasion assay and flow cytometry were used to detect the proliferation, invasion and apoptosis of treated cells, respectively. A Nimblegen genome-wide expression profile chip was used to evaluate gene expression changes in 125I seed-treated A549 cells. Validation studies were performed using phosphorylated protein chip technology, Western blot, nude mouse tumor xenograft assay and immunohistochemical experiments. All statistical analyses were performed using unpaired Student’s t-tests and Kruskal-Wallis test. Results: Irradiation with 125I seed inhibited A549 cell proliferation and invasion and induced apoptosis (primarily early apoptosis). Irradiation with 125I also caused the downregulation of p38MAPK, degradation of MDM2 (mouse double-minute 2 homolog) and higher expression of p53, which eventually resulted in non-small cell lung cancer cell apoptosis. Conclusion: 125I seed irradiation activated the p38MAPK/MDM2/p53 signaling pathway and promoted non-small cell lung cancer cell apoptosis. Future clinical studies targeting this signal may provide a new potential therapeutic approach for non-small cell lung cancer.